A small exercise — 2 Comments

  1. ((-1)²)^(1/2)) can’t be reduced to (-1)^(2*(1/2)), it’s not commutative … it would be akin to say that sqrt ((-1)²)=1 equals (sqrt(-1))²=i²=-1

    • That is correct, visitor Pelele!!!
      The rule (a^b)^c = a^(bc) is not valid when a is negative, which some people tend to forget.
      (But it is always valid when a is greater than zero.)

Leave a Reply

Your email address will not be published.

HTML tags allowed in your comment: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>